Mobiliser la langue pour faire entendre la périphérie : étude comparée des mouvements nationalitaires bretons et sorabes au prisme de leurs revendications linguistiques - Jeanne Toutous (Lengas)
This article compares the processes of convergence or dissonance between nationalist movements and language movements. We aim at discussing the linguistic and militants situations in two regions that are not often compared, and which are also affected by two levels of linguistic power relations. While the research in political science tends to focus on nationalist movements on a regional scale, little research has been done to date on the phenomena of competition between activists of different regional languages within the same region. By studying language claims in their context in Brittany (France) and Lusatia (Germany), we put forward the hypothesis that nationalist movements value one of the two regional languages to the detriment of the second. While activists of the Breton language (in Brittany) and the Upper Sorbian language (in Lusatia) tend to invest the regional territory and community institutions in the name of regional society as a whole, activists of the Breton (Brittany) and Lower Sorbian languages try to distance themselves from the instituting nationalist narratives by relying on diffuse and unstable repertoires of action, bearing witness to a process of double minoritarisation.